PdSe2 Multilayer on Germanium Nanocones Array with Light Trapping Effect for Sensitive Infrared Photodetector and Image Sensing Application - Luo, Lin‐Bao; Wang, Di; Xie, Chao; Hu, Ji‐Gang; Zhao, Xing‐Yuan; Liang, Feng‐Xia (Advanced functional materials, 2019)
In this study, a sensitive infrared photodetector (IRPD) composed of a germanium nanocones (GeNCs) array and PdSe2 multilayer is presented, which is obtained by a straightforward selenization approach. The as‐assembled PdSe2/GeNCs hybrid heterojunction exhibits obvious photovoltaic behavior to 1550 nm illumination, which renders the IRPD a self‐driven device without external power supply. Further device analysis reveals that the PdSe2/GeNCs hybrid based IRPD exhibits high sensitivity to 1350, 1550, and 1650 nm illumination with excellent stability and reproducibility. The responsivity and external quantum efficiency is as high as 530.2 mA W−1 and 42.4%, respectively. Such a relatively good device performance is related to the strong light trapping effect of GeNCs array, according to the theoretical simulation based on finite‐difference time‐domain. It is also found that the IRPD shows an abnormal sensitivity to IR illumination with a wavelength of 2200 nm. Finally, the present individual IRPD can also record the simple “F” image produced by 1550 nm, suggesting the promising application of the PdSe2/GeNCs hybrid device in future infrared optoelectronic systems. A highly sensitive infrared light photo‐detector is fabricated by transferring multilayer PdSe2 on a germanium nanocones array with a strong light‐trapping effect. The as‐assembled PdSe2/GeNCs hybrid heterojunction devices can also record simple near‐infrared images.